Continuous-Wave Crystalline Laser at 714 nm via Stimulated Raman Scattering and Sum Frequency Generation - Chien-Yen Huang; Bo-Cheng Guo; Zi-Xuan Zheng; Chia-Han Tsou; Hsing-Chih Liang; Yung-Fu Chen (Crystals, 2022)
A compact high-power continuous-wave (CW) laser at 714 nm is originally developed via intracavity stimulated Raman scattering (SRS) and sum frequency generation (SFG). The fundamental wave at 1342 nm and the first-Stokes Raman wave at 1525 nm are generated by using a Nd:YVO4 and a undoped YVO4 crystals, respectively. Compared to the self-Raman laser, the separation of the gain media for generating the fundamental and Raman waves can effectively reduce the thermal lens effect in the Nd:YVO4 crystal and efficiently enhance the SRS in the undoped YVO4 crystal. Furthermore, the undoped YVO4 crystal is coated to act as a high-reflection mirror for minimizing the cavity losses. At a pump power of 40 W, the output power at 714 nm can reach 1.8 W. The present compact design for CW laser source at 714 nm is believed to be practically useful for laser cooling and trapping of radium.